IMMUNOREACTIVITY OF CHILDREN OF DIFFERENT AGES WITH THE CEREBRO-ASTHENIC SYNDROME, WHO WERE PREMATURELY BORN WITH PERINATAL DEFEAT OF CENTRAL NERVOUS SYSTEM - Popov, M. M.; Olenych, V. B.; Savvo, O. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The immune status and nature of immune frustration of children of different ages with the cerebral asthenic syndrome (CAS), who were prematurely born with perinatal defeat of the central nervous system (CNS) was studied. The obtained data argue that these children have the expressed imbalance among Тh-cages (Th1, Th2, Treg) and cytokines that shows the potential risk of inadequate reaction of these children on infectious and noninfectious immunogenes.